AN INVESTIGATION INTO UTILIZATION, BELIEFS AND PRACTICE OF INDIGENOUS MEDICINE IN SRI LANKA - Padmasiri, G. R. (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Most countries pose their own indigenous knowledge systems. Native knowledge on indigenousmedicine is one of the knowledge systems widely used in many countries in Asia and Africa. In some countries, 80% ofthe population depend on indigenous medicine for primary health care. Sri Lanka is an island enriched with a wellestablishedindigenous medical system.Materials and Methods: The objectives of the study were to identify characteristics, usage patterns, and perceptions ofcommunities concerning indigenous medicine. Beneficiaries of indigenous medicine were selected through purposivesampling for this study. The data were collected through a documentary survey and interviews.Results: The study identified that the indigenous medical system of the country is called ‘DeshiyaChikitsa,’ ‘SinhalaVedakama,’ or ‘Hela Vedakama,’ which encompass ritual healing practices, astrology, religious observances, andspiritual powers. Different approaches of people including the use of domestic medicine, obtaining the assistance ofastrology, and rituals were identified. Regardless of age, level of education, or employment, communities trustindigenous medicine as a primary or a secondary option on the health care system of the country. The survey identifiedthe growing demand for the indigenous medicine.Conclusion: Around 60 to 70% of the rural population which is comprise 77.3% of total population relies onindigenous medicine. Domestic medicine, astrology and rituals associated with indigenous medicine plays a vital rolein people’s health care process. Experts in indigenous medicine are scattered in the country.